Performance of Archivist in Library and Archive Departement of Batu City - Mardhotillah, Annisa Ilmi; Asari, Andi; Nurchasanah, Nurchasanah (CV. Bimbingan Belajar Assyfa, 2024)
The archivists in the Batu City Department of Library and Archives play a pivotal role in ensuring efficient archival services for the community. This study evaluates their performance, focusing on record acquisition, management, preservation, and service delivery. Utilizing a qualitative approach, the research incorporates observations, interviews with 15 archivists, and examination of departmental records over six months. The analysis includes data reduction, modeling, and verification processes to derive comprehensive insights. The findings reveal that the archivists’ effectiveness is significantly influenced by their educational background, ongoing training, and accumulated work experience. Despite their competence, a notable gap exists in the formal academic qualifications related to archival studies. Moreover, disparities in training access further exacerbate performance inconsistencies. Consequently, while the current procedures are well-adhered, improvements are essential. To address these challenges and enhance expertise, it is recommended that archivists with formal archival education be recruited. Additionally, implementing a structured training program that offers equal participation opportunities can bridge the skill gap. Lastly, reducing non-core tasks will enable archivists to focus on their primary responsibilities, improving overall service delivery. These measures are anticipated to positively impact the department’s ability to meet community needs and enhance organizational efficiency.